Evaluation of the Safety and Efficacy of the Open Entry Technique in Laparoscopic Surgery - Elmehdawi, Haitham; Abuzeid , Issa (AlQalam Journal of Medical and Applied Sciences, 2025)
Laparoscopic surgery has significantly improved patient recovery and reduced morbidity. However, the method of entry into the peritoneal cavity remains a concern due to potential complications. This study revisits an open entry modification that utilizes the umbilical cicatrix tube for fascia incision and blunt dissection, aiming to assess its safety, efficacy, and applicability relative to existing laparoscopic entry methods. A total of 400 laparoscopic cholecystectomies were performed using the proposed technique. Data on patient demographics, body mass index (BMI), previous surgeries, and complications were collected. Results showed no vascular or visceral injuries, and zero incidence of gas leakage. The technique proved effective across surgeon experience levels and in patients with prior abdominal surgery and obesity (16% with BMI > 30). The open access technique demonstrated safety, efficacy, and ease of learning for surgeons of varying experience. It is suitable for obese patients and those with previous abdominal surgeries.